Studies on stability of chilli genotypes at different fertility levels under terai zone of West Bengal - J C Jana, S Datta, (Journal of Spices and Aromatic Crops, 2014)
An experiment was carried out to study the stability of 15 chilli genotypes at five fertility levels (0%, 50%, 100%, 150% and 200% of recommended dose of fertilizer) during rabi season of 2006–07 and kharif season of 2007. Pooled analysis of variance showed the presence of significant genetic variability among the genotypes for all the characters studied. Among the different early flowering genotypes, ‘CA-29’ and ‘CA-30’ were specifically adapted to the unfavourable environment and ‘Diamond F1’ and ‘Pusa Sadabahar’ were adapted to the favourable environment. None of the genotypes showed absolute stability with respect to fruit length under different environments. With respect to number of fruits, ‘Pusa Sadabahar’ was stable under different environments. With respect to yield, 12 genotypes showed S2di value significantly greater than zero which indicated the unstability for this trait. Among the high yielding genotypes, ‘Ulka 686 F1’, ‘Jwalan’, ‘CA-29’, ‘CA-48’ and ‘CA-47’ and low yielder genotype had regression value of > 1 which indicated that they showed better response under favourable environment. However, deviation from regression value (S2di) was significant which indicated that their performance among the environment was unpredictable. ‘Chilli Philhal’ and ‘Pusa Jwala’ produced lower yield but these genotypes were adapted to unfavourable environment. The rabi crop showed its superiority over kharif crop with respect to yield and its attributing characters.